Behavioral responses of Chrysomya megacephala to natural products - Bunchu N. (2014)
Knowledge of the behavioral responses of medically important flies to natural stimuli is critical for the development of vector control strategies. We designed, constructed, and operated the dual-choice wind tunnel to investigate the behavioral responses of the blowfly, Chrysomya megacephala (Diptera: Calliphoridae), toward two important extrinsic factors (wind speed and olfactory stimuli) that affect the flight behavior of these flies. The dual-choice wind tunnel appeared as a "T-box," consisting of two stimulus partitions and one median release partition. The correlation between wind speed and fly response showed a marked relationship, with the wind speed set at 0.5 m/s being the optimal speed. Of the 72 natural products tested, 24-all having high protein content-attracted flies at the level of greater than 50% in the rearing cages during preliminary tests, thus allowing further investigation in the dual-choice wind tunnel to further assess these responses. The behavioral response between flies exposed to the screening odors in a rearing cage and those exposed in the dual-choice wind tunnel showed a similar trend. One-day-tainted pork viscera yielded the greatest positive response among natural products tested, attracting greater than 90% of the flies included in the test population. One-day-tainted pork viscera exhibited the highest potency (1.578), exceeding 1-day-tainted beef liver, which is commonly used as the standard bait for blowflies. The usefulness and practical applications of the dual-choice wind tunnel for further investigations are also discussed. © 2007 Springer-Verlag.